Genotypic Performance of Kenyan Rice Cultivars for Grain Yield and Quality - Denis, Bryan Elwich John; Ngugi, Kahiu; Kimani, J.M. (Journal of Agricultural Studies, 2022)
Rice is the third most important staple food in Kenya after maize and wheat and it is mostly grown by small scale farmers both for food and cash under irrigated and rainfed production systems. In this study, fourteen F 2.3 segregating populations together with their parental lines, were evaluated during the long and short rainy seasons of 2016/2017 at the Mwea Research Station (KALRO) in a randomized complete block design of three replications for grain yield, quality and agronomic traits. There were significant differences among genotypes for all the traits studied. Genotypes, Nerica 1, Nerica 2 and Basmati-370 matured earliest, whereas genotype, Basmati-370 gave the highest grain yields in both seasons. The F1 generations of crosses of Dourado x Nerica 3 and Mwur 4 x Nerica 3 had the highest positive Specific Combining Ability (SCA) gene effects for panicle length, days to flowering and grain yield. However in the F 2.3 generations, the progenies of Nerica 2 x Basmati-370 and Nerica 3 x Basmati-370 had the highest grain yields. Generations of Nerica 10 x Mwur 4 crosses, had the longest grains whereas the Basmati-370 genotype had the strongest aroma. Generations of NERICA 3 x Basmati 370 and NERICA 2 x Basmati 370 crosses were of mild aroma, but those of K1-99 x KOMBOKA and NERCA 10 were non aromatic. Grain yield was positively significantly correlated with number of productive tillers, number of filled grains and 1000 grain weight indicating that these traits could serve as secondary selection indices for yield. It is inferred that breeding rice cultivars with improved traits for grain yield, long grain and strong aroma would benefit from the utilization of parental and population germplasm identified in this study, in the pursuit of filling the current rice production deficit in the Kenyan consumer markets.